Multicentric sinus histicytosis (Rosai-Dorfman Disease): Computed tomography, magnetic resonance imaging findings - S H Chandrashekhara; Y C Manjunatha; Sandeep Muzumder; Amit Bahl; Prasenjit Das; Vaishali Suri; Sanjay Thulkar (Indian Journal of Medical and Paediatric Oncology)
Sinus histicytosis (Rosai-Dorfman disease) is a rare, benign granulomatous disease that typically presents with massive cervical lymphadenopathy. Extranodal involvement along with concomitant nodal disease occurs in about 43% of cases. We present a unique case of a 30-year-old male with cervical, retroperitoneal lymphadenopathy, associated with renal and pituitary sellar masses.